Eco-impacts evaluation in the greening approach adopted by the Romanian Public University - Andrew Walker (African Journal of Environmental Economics and Management, 2016)
The present paper compared the results generated from 2 Eco-Indicators (Ecological Footprint and Carbon Footprint) as important markers in future greening strategy evaluation that will be adopted for the first time by a Romanian Eastern Public University (UGAL). The calculated amount of EF value per students is 0.818 gha and per capita is 0.760 gha. The Eco-Indicators values are more reasonable in compare with the recommended amount by the WWF (the average is 1.9 gha per capita) and also with the values which are reported by the other universities. Energy, transportation systems and foods are the most important portions of the total EF value.